An evaluation of baseline risk factors predicting severity in juvenile idiopathic arthritis associated uveitis and other chronic anterior uveitis in early childhood. Issue 1 (1st January 2002) - Edelsten, Clive; Lee, Vickie; Bentley, Christopher R; Kanski, Jack J; Graham, Elizabeth M
Abstract : Background/aims: The clinical course for childhood chronic anterior uveitis can vary from mild, self limiting disease to bilateral blindness. The purpose of this study was to identify those risk factors at onset that predict disease severity. Methods: A retrospective case note review of all patients with painless anterior uveitis diagnosed from 1982 to 1998. Patients were divided into two cohorts based on route of referral, diagnosis, and compliance with treatment. The standard cohort consisted of only those diagnosed from routine screening of juvenile idiopathic arthritis. Results: Complications—cataract surgery, ocular hypertension treatment, and visual acuity <6/24. Remission: inactive uveitis on no topical treatment for >6 months. Results—163 patients were included. 34 patients (21%) developed at least one complication. The most significant predictor of complications was severe disease at onset (p = 0.001). Other factors included uveitis at the first examination (p = 0.034), membership of the non-standard cohort (p = 0.0001), non-oligoarticular disease (p = 0.02), and late onset arthritis (p = 0.024). Male sex was associated with increased complications in the standard cohort (p = 0.001). Factors predisposing to remission included membership of the standard cohort (p = 0.003), onset after 1990 (p = 0.016), white race (p = 0.015), mild disease onset (p = 0.003), and a long gap between arthritis and uveitis onset (p = 0.015). Conclusions: It is possible to characterise the severity of those with childhood chronic anterior uveitis at the onset of disease. The majority of patients remit without visually disabling complications. It may be possible to reduce the complication rate by targeting aggressive immunosuppression on high risk patients before complications develop.